2018
DOI: 10.1111/jopy.12385
|View full text |Cite
|
Sign up to set email alerts
|

Shyness and sociability among extremely low birth weight survivors in the third and fourth decades of life: Associations with relationship status

Abstract: Relatively higher shyness among ELBW survivors in adulthood suggests that stressful pre- and early postnatal environments may have lasting effects on personality development. However, later social influences such as relationship status may attenuate some types of shyness in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Because of the higher rates of psychological problems (Mathewson et al, 2017), cautiousness (Waxman et al, 2013), and shyness (Schmidt et al, 2008; Xu et al, 2019) observed into adulthood among ELBW survivors, it is surprising that ELBW individuals did not report higher inhibition in their 30s. One potential explanation for this finding is that shyness, cautiousness, and behavioral inhibition represent fundamentally different constructs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the higher rates of psychological problems (Mathewson et al, 2017), cautiousness (Waxman et al, 2013), and shyness (Schmidt et al, 2008; Xu et al, 2019) observed into adulthood among ELBW survivors, it is surprising that ELBW individuals did not report higher inhibition in their 30s. One potential explanation for this finding is that shyness, cautiousness, and behavioral inhibition represent fundamentally different constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while the short-term stability of the BIS/BAS scales over 2 (Carver & White, 1994) and 6 (Sutton & Davidson, 1997) months is modest to very good (with correlations of .59 to .87, respectively), the long-term stability of the BIS/BAS scales beyond 6 months, to the best of our knowledge, has not been explored. Because constructs conceptually and empirically related to BIS/BAS (e.g., shyness and sociability, respectively) are known to remain stable over a 10-year period in ELBW and NBW adults (Waxman et al, 2013; Xu et al, 2019), we predicted that the BIS/BAS scales would also remain stable between ages 22–26 and 30–35 years.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical history, diazoxide-responsiveness was defined as the ability to achieve elevated intravenous glucose and maintain normoglycemia ( 12 ). Low birth weight was determined based on birth weight adjusted by the gestational age ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additional work has found that prematurity (Tessier, Nadeau, Boivin, & Tremblay, 1997) and prenatal corticosteroid exposure (betamethasone; Erni, Shaqiri, La Marca, Zimmermann, & Ehlert, 2012) are correlated with more social withdrawal and social-evaluative stress, respectively, in childhood (age 10–12 years). Still other studies have found that lower birth weight was associated with higher levels of introversion (Allin et al, 2006; Hertz, Mathiasen, Hansen, Mortensen, & Greisen, 2013; Pesonen et al, 2008), behavioral inhibition (Pyhälä et al, 2009), social withdrawal (Eryigit-Madzwamuse, Strauss, Baumann, Bartmannm, & Wolke, 2015; Hack et al, 2004) and shyness in young adulthood (early 20s; Schmidt, Miskovic, Boyle, & Saigal, 2008) and adulthood (early 30s; Waxman, Van Lieshout, Saigal, Boyle, & Schmidt, 2013; Xu Poole, Van Lieshout, Saigal, & Schmidt, 2018), as well as harm avoidance in later adulthood (age 60 years; Lahti et al, 2008).…”
mentioning
confidence: 99%